Characteristics and properties of a polysaccharide isolated from Wolfiporia cocos as potential dietary supplement for IBS - Yang, Xuan; Lu, Shun; Feng, Yuhan; Cao, Chongjiang; Zhang, Yanliang; Cheng, Shujie (Frontiers in Nutrition, 2023)
Introduction As low FODMAP (Fermentable oligosaccharides, disaccharides, monosaccharides and polyols) diet therapy is recommended for most of Irritable Bowel Syndrome (IBS) patients, the consequent insufficient of dietary fibers (DFs) intake exert an adverse impact on intestinal health. It is necessary to find suitable DFs for IBS patients. Methods This study extracted a water-insoluble polysaccharide from Wolfiporia cocos (WIP) by alkali-extraction and acid-precipitation method. Its molecular weight was detected by high performance gel permeation chromatography (HPGPC) analysis. The structure of WIP was analyzed by Fourier transform infrared (FT-IR) spectrum, Nuclear Magnetic Resonance (NMR) spectra and X-ray diffraction (XRD). The properties related to stability, digestion, viscosity, osmotic activity, adsorption and fermentation were investigated, aimed to explore the feasibility of WIP as a new DF supplement for patients with IBS. In addition, 16S rRNA sequencing analysis was conducted to explore its effects on IBS-related gut microbiota. Results and Discussion The results showed that WIP had a single homogeneous composition and the molecular weight was 8.1 × 103 Da. WIP was indicated as a kind of pyranose form with β anomeric configuration and the main chain of WIP was 1,3-β-glucan with amorphous structure. In addition to good thermal stability, WIP also has low bioavailability and can reach the colon mostly without being digested. Moreover, the low viscosity and osmotic activity, the high water- swelling and water/oil-holding capacity, fructose adsorption capacity and poor fermentation performance of WIP demonstrated that it is suitable for IBS patients. It is worth noting that WIP regulates IBS associated gut microbiota effectively, such as the abundance of Lachnospiraceae and Prevotella. These findings provide a theoretical basis for the development of WIP as a dietary supplement for IBS patients with low FODMAP diet therapy. GRAPHICAL ABSTRACT